Meningkatnya Perilaku Sadar Gizi Setelah Pemberian Wawasan Gizi Seimbang Pada Remaja SMP Kelas VII Di SMP Negeri 1 Mojokerto - Diya Agustina (FKIP, Universitas Billfath Lamongan, 2020)
The students need insight into balanced nutrition to avoid nutritional problems such as stunting (short body), micronutrient deficiency, especially anemia (iron deficiency) and malnutrition. The problem in this study is how nutritionally conscious behavior and student learning outcomes after obtaining balanced nutrition insight. The aim of this study is to obtain improvement in students' nutrition awareness and improved learning outcomes about nutrition and energy in food. The results of this research indicate an increase in nutritional awareness behavior after gaining insight into balanced nutrition, namely there is an increase in the number of students who have understood the importance of consuming milk everyday (71%); always breakfast (52%); have a diet with balanced nutritional value (18%); understanding of the importance of vegetables and fruit (40%); washing hands before eating (78%); brush your teeth before going to sleep (23%); exercise twice a week (20%); monitor body weight (50%).